2023
DOI: 10.1186/s12989-023-00560-8
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene nanobeads exacerbate chronic colitis in mice involving in oxidative stress and hepatic lipid metabolism

Juan Ma,
Yin Wan,
Lingmin Song
et al.

Abstract: Background Nanoplastics (NPs) are omnipresent in our lives as a new type of pollution with a tiny size. It can enter organisms from the environment, accumulate in the body, and be passed down the food chain. Inflammatory bowel disease (IBD) is a nonspecific intestinal inflammatory disease that is recurrent and prevalent in the population. Given that the intestinal features of colitis may affect the behavior and toxicity of NPs, it is imperative to clarify the risk and toxicity mechanisms of NPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Indeed, further recent evidence in mouse models confirms these suspicions. It was observed that PS-NPs aggravate inflammation and intestinal injury in mice with chronic colitis [ 102 ]. Specifically, mice subjected to sodium dextran sulfate (DSS) exposures were subsequently fed via gastric tube with water containing 100 nm polystyrene nanospheres (PS-NPs, at concentrations of 1 mg/kg, 5 mg/kg, and 25 mg/kg) for 28 consecutive days.…”
Section: Mnps and The Intestinal Systemmentioning
confidence: 99%
“…Indeed, further recent evidence in mouse models confirms these suspicions. It was observed that PS-NPs aggravate inflammation and intestinal injury in mice with chronic colitis [ 102 ]. Specifically, mice subjected to sodium dextran sulfate (DSS) exposures were subsequently fed via gastric tube with water containing 100 nm polystyrene nanospheres (PS-NPs, at concentrations of 1 mg/kg, 5 mg/kg, and 25 mg/kg) for 28 consecutive days.…”
Section: Mnps and The Intestinal Systemmentioning
confidence: 99%